2008
DOI: 10.1111/j.1600-0404.2008.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized trial of low-dose topiramate vs propranolol in migraine prophylaxis

Abstract: This study demonstrated that both low-dose topiramate and propranolol could significantly reduce migraine headache frequency, intensity, and duration. However, compared with propranolol, low-dose topiramate showed better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…Two additional Class I studies report topiramate is as effective as propranolol 16 or sodium valproate, 17 drugs previously established as effective for migraine prevention. In the first study, subjects given topiramate 50 mg/day had reduced mean migraine frequency (episodes/month) from baseline (6.07 Ϯ In a crossover Class I trial (2-month washout between therapies) comparing topiramate 50 mg/day with sodium valproate 400 mg/day, both groups showed improvement from baseline in headache frequency, intensity, and duration.…”
mentioning
confidence: 99%
“…Two additional Class I studies report topiramate is as effective as propranolol 16 or sodium valproate, 17 drugs previously established as effective for migraine prevention. In the first study, subjects given topiramate 50 mg/day had reduced mean migraine frequency (episodes/month) from baseline (6.07 Ϯ In a crossover Class I trial (2-month washout between therapies) comparing topiramate 50 mg/day with sodium valproate 400 mg/day, both groups showed improvement from baseline in headache frequency, intensity, and duration.…”
mentioning
confidence: 99%
“…A prior study testing low-dose topiramate vs propranolol demonstrated that both low-dose topiramate and propranolol significantly reduced migraine headaches. 20 Although this study did not include a placebo comparator, other placebocontrolled trials have shown propranolol and topiramate each as efficacious monotherapy in people with migraine. 9 The CMTT was performed in a large cohort of practices that were part of the National Institute of Neurological Disorders and Stroke Clinical Research Collaboration.…”
Section: Continuous Headache N (%)mentioning
confidence: 99%
“…Furthermore, in topiramate group, patients complained of more adverse effects than propranolol group (23.4% vs. 14.3%). So, comparative studies of propranolol with topiramate showed that topiramate was more effective especially in Iran (Ashtari et al 2008) 13 but present study showed that, propranolol is more effective than topiramate in migraine prophylaxis probably due to poor metabolism of propranolol in our regional context (Correia, 2009) 18 .…”
Section: Discussionmentioning
confidence: 78%
“…A good number of the study patients were 18-25 years age group in both groups (42.6% vs. 42.9% 13 found that the topiramate group showed more reduction in migraine frequency than propranolol group. These results are not similar to this study probably due to racial variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation